Impact of Oxygen Deficiency on the Electrochemical Performance of K2NiF4‐Type (La1−xSrx)2NiO4−δ Oxygen Electrodes. Issue 3 (28th December 2016) - Kravchenko, Ekaterina; Zakharchuk, Kiryl; Viskup, Alexander; Grins, Jekabs; Svensson, Gunnar; Pankov, Vladimir; Yaremchenko, Aleksey
Abstract: Perovskite‐related (La1− x Sr x )2 NiO4− δ ( x =0.5–0.8) phases were explored for possible use as oxygen electrodes in solid electrolyte cells with a main focus on the effect of oxygen deficiency on the electrocatalytic activity. (La1− x Sr x )2 NiO4− δ solid solutions were demonstrated to preserve the K2 NiF4 ‐type tetragonal structure under oxidizing conditions. Acceptor‐type substitution by Sr is compensated by the formation of oxygen vacancies and electron holes and progressively increases high‐temperature oxygen nonstoichiometry, which reaches as high as δ =0.40 for x =0.8 at 950 °C in air. The electrical conductivity of (La1− x Sr x )2 NiO4− δ ceramics at 500–1000 °C and p (O2 )≥10 −3  atm is p‐type metallic‐like. The highest conductivity, 300 S cm −1 at 800 °C in air, is observed for x =0.6. The average thermal expansion coefficients, (14.0–15.4)×10 −6  K −1 at 25–900 °C in air, are sufficiently low to ensure the thermomechanical compatibility with common solid electrolytes. The polarization resistance of porous (La1− x Sr x )2 NiO4− δ electrodes applied on a Ce0.9 Gd0.1 O2− δ solid electrolyte decreases with increasing Sr concentration in correlation with the concentration of oxygen vacancies in the nickelate lattice and the anticipated level of mixed ionic–electronic conduction. However, this is accompanied by increasing reactivity between the cell components and necessitates the microstructural optimization of the electrode materials to reduce the electrode fabrication temperature. Abstract : Deficiency promotes electrochemistry : The oxygen nonstoichiometry, electrical properties, and electrochemical activity of Sr‐rich (La1− x Sr x )2 NiO4− δ were studied for its use as an oxygen electrode in solid oxide fuel/electrolysis cells. Increasing Sr content is demonstrated to increase the oxygen deficiency, thus promoting mixed ionic–electronic conductivity and decreasing the polarization resistance of the (La1− x Sr x )2 NiO4− δ electrodes.